INFLUENCE OF WORK ENVIRONMENT, MOTIVATION, AND DISCIPLINE ON EMPLOYEE PERFORMANCE (Jurnal Ipteks Terapan, 2022)
Test and analyze the influence of Work Environment, Motivation, and Discipline on Employee Performance of PT. Raja Putra Manggala is the aim of this research. The quality of Human Resources contributes to maximizing the results in the success of a company. The work environment is one of the other factors that affect employee performance because of the place where employees do their work. In addition, motivation also plays an important role in fostering employee morale, without motivation given to employees it can reduce employee performance, and a lack of discipline can lead to poor time management and will affect employee performance. A total of 175 employees are the population and 121 employees are the sample in this study. Multiple linear regression analysis is a technique in this research method. In testing this hypothesis, the calculation results obtained a value of tcount < ttable (1.890 < 1.980) and a significant value of 0.003 > 0.05 partially, the value of tcount < ttable (0.816 < 1.980) and a significant value of 0.021 > 0.05 partially, the value of tcount > ttable (2.052 > 1.980) and the significant value is 0.001 < 0.05 partially, the Fcount (39.387) > Ftable (2.68) and 0.000 < 0.05 for the probability of significance. Adjusted R Square value of 0.490 is obtained from the coefficient test results which means that the variation in the dependent variable is 49.0% as explained from other variables such as compensation, promotion, training, leadership, and so on which were not examined in this study. This study concludes that simultaneously Work Environment, Motivation, and Discipline on Employee Performance of PT. Raja Putra Manggala and partially the Work Environment, Motivation, and Discipline Against Employee Performance PT. Raja Putra Manggala